Digital Business Transformation in the Era of Artificial Intelligence: Strategies, Opportunities, and Challenges for Enhancing Business Competitiveness - Ahmad Yahya Hamiduddin (CV. Civiliza Publishing, 2026)
Digital business transformation in the era of Artificial Intelligence (AI) has become a key driver for enhancing business competitiveness amid increasingly intense global competition and rapid technological advancement. The implementation of AI enables organizations to optimize business processes through automation, advanced data analytics, personalized customer services, and data-driven decision-making. This article aims to examine strategies for implementing AI in digital business transformation, identify the opportunities available to business organizations, and analyze the challenges associated with AI adoption. The study employs a literature review method by analyzing relevant academic journals, books, and research reports on digital transformation and artificial intelligence. The findings indicate that AI implementation significantly improves operational efficiency, productivity, product and service innovation, and customer experience, thereby creating sustainable competitive advantages for businesses. However, AI adoption also faces several challenges, including limited digital infrastructure, high investment costs, a shortage of skilled human resources, data security concerns, and ethical issues related to AI utilization. Therefore, an integrated strategy involving digital infrastructure development, workforce capacity building, supportive government policies, and collaboration among businesses, academia, and technology providers is essential to ensure successful and sustainable AI-driven digital business transformation.